Indication of cowpea cultivars for the production of dry grain in the state of Ceará - Linco de Souza Tomaz, Francisco (Revista Ciência Agronômica, 2021)
The aim of this work was to evaluate the interaction between genotypes and environments, as well as toindicate, for the state of Ceará, superior cowpea cultivars in terms of adaptability, stability and productivity of dry grains. Theexperiments were conducted in four different municipalities in the state of Ceará: Crateús, Madalena, Bela Cruz and Limoeiro doNorte; two tests carried out in Crateús (irrigated and rainfed), totaling five assessment environments. The experimental designused in each assay was randomized blocks with 12 genotypes and four replications. Analysis of variance and path analysis wereperformed, and the averages of the quantitative characters were grouped by the Scott-Knott test. After detecting the significanceof the genotype x environment interaction, the adaptability and phenotypic stability of the genotypes were analyzed using theGGE biplot methodology. The municipality of Crateús, in the irrigated system, was discriminative and representative, and canbe considered ideal for genotype evaluation. The cultivars BRS Pajeú and BRS Potengi can be recommended for cultivation inthe state of Ceará due to their high productivity of dry grains, adaptability and stability, and for having excelled in most of theproduction components. The number of pods per plant had the greatest direct effect on grain yield.